Literacy Dice Puzzle Learning Media to Improve Literacy Skills of Grade V Elementary School Students - Mila Indriati; Bagus Amirul Mukmin; Kukuh Andri Aka; Rian Damariswara (Jurnal Pendidikan dan Pengajaran, 2025)
The lack of reading culture at home and in the surrounding environment impacts low student literacy. Based on this, this study aims to develop a game-based learning media, "Teka-Teki Dadu Literasi", to improve the literacy skills of grade V elementary school students that are valid, practical, and effective. This study uses the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The methods used in collecting data are interviews, observations, questionnaires and tests. The instruments used in the study were questionnaire sheets and tests. The subjects of the study were learning media experts. The trial subjects were in two stages: limited trials and extensive trials by students and teachers. The data analysis technique in this study used a quantitative and qualitative descriptive approach. The study results were the validity test results from the learning media expert, who obtained a score of 83.07%, so it was included in the "Very Good" criteria. The results of the practicality test by the teacher obtained a score of 92% (very valid). The results of the limited trial by students were 100% (very valid). The results of the extensive trial by students were 98.77% (very valid). The effectiveness test results showed that the "Literacy Dice" media effectively improved students' literacy skills, with an average increase of 68,2%. This shows that this learning media is suitable for supporting the literacy learning process. The implication of this research is that the game-based learning media "Literacy Dice Puzzle" that was developed can be used in elementary school learning.